Identification of Wolbachia-Responsive miRNAs in the Small Brown Planthopper, Laodelphax striatellus - Liu, Lei; Zhang, Kai-Jun; Rong, Xia; Li, Ya-Ying; Liu, Huai (Frontiers in Physiology, 2019)
Laodelphax striatellus is naturally infected with the Wolbachia strain wStri, which induces strong cytoplasmic incompatibility of its host. MicroRNAs (miRNAs) are a class of endogenous non-coding small RNAs that play a critical role in the regulation of gene expression at post-transcriptional level in various biological processes. Despite various studies reporting that Wolbachia affects the miRNA expression of their hosts, the molecular mechanism underlying interactions between Wolbachia and their host miRNAs has not been well understood. In order to better understand the impact of Wolbachia infection on its host, we investigated the differentially expressed miRNAs between Wolbachia-infected and Wolbachia-uninfected strains of L. striatellus. Compared with uninfected strains, Wolbachia infection resulted in up-regulation of 18 miRNAs and down-regulation of 6 miRNAs in male, while 25 miRNAs were up-regulated and 15 miRNAs were down-regulated in female. The target genes of these differentially expressed miRNAs involved in immune response regulation, reproduction, redox homeostasis and ecdysteroidogenesis were also annotated in both sexes. We further verified the expression of several significantly differentially expressed miRNAs and their predicted target genes by qRT-PCR method. The results suggested that Wolbachia appears to reduce the expression of genes related to fertility in males and increase the expression of genes related to fecundity in females. At the same time, Wolbachia may enhance the expression of immune-related genes in both sexes. All of the results in this study may be helpful in further exploration of the molecular mechanisms by which Wolbachia affects on its hosts.